2021
DOI: 10.1039/d1bm01035b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced clearing of Candida biofilms on a 3D urothelial cell in vitro model using lysozyme-functionalized fluconazole-loaded shellac nanoparticles

Abstract: We report a novel 3D urothelial clusteroid/fungal biofilm co-culture model for the advanced testing of antifungal nanotechnologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…7). 70 The robust biofilm reduction by the formulated nanoparticles was attributed to the ability of Alcalase and lysozyme to break down and cleave the glycoprotein cross-linked components of the EPS.…”
Section: Discussionmentioning
confidence: 99%
“…7). 70 The robust biofilm reduction by the formulated nanoparticles was attributed to the ability of Alcalase and lysozyme to break down and cleave the glycoprotein cross-linked components of the EPS.…”
Section: Discussionmentioning
confidence: 99%
“…3D human cell culture and tissue studies have been indicated as more adequate than in vitro models for testing the significance of clinical treatments as they provide the opportunity for bacterial and fungal pathogens to interact with host tissues. 143,156 Ex vivo porcine wound models have been used previously and provide a close physiological comparison to human wound tissue for use with clinically relevant bacteria. 157 In vivo models provide a further level of relevance, allowing the contribution of host factors such as ischemia and necrosis on biofilms to be assessed.…”
Section: Future Perspectivementioning
confidence: 99%
“…The demand for new treatments will likely drive the manufacture and application of antimicrobial NPs mimicking what has happened with anti-cancer NPs. Regarding treatments of AMR pathogens in surface chronic wounds, 26,27,139,143,147,154 and as recently proposed for fungal 155 and chronic bladder infections 156 with active antimicrobial nanoformulations, some of the issues related to the intravenous delivery of NPs are not so acute which would allow a potentially faster route to the market.…”
Section: Challenges and Routes To Clinical Acceptance Of Nanotechnolo...mentioning
confidence: 99%
“…189 In addition, amphotericin B could also be encapsulated in the Alcalase 2.4 L FG-coated shellac nanoparticles, which are less toxic to adult keratinocytes cells, has higher efficacy against Candida albicans, and may be used for the treatment of fungal biofilm infections in a clinical setting. 190 Wang et al 191 found that fluconazole-loaded shellac nanoparticles coated with lysozyme, prepared using the same method, could effectively remove C. albicans biofilms formed on the 3D layers of urothelial cell clusters. Moreover, Wang et al 23 used rice proteins and shellac to fabricate composite nanoparticles by dissolving these two biopolymers at pH 12 and then adjusting the pH to 7.…”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%